Migrants or Expatriates? Americans in Europe - Koppenfels, Amanda Klekowski von.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book examines the migration, integration and transnational activity of overseas Americans – American migrants – in France, Germany and the UK. It examines the reasons for their migration, introduces the concept of 'accidental migrant' and explores the question of overseas Americans' integration and identity formation.
Keywords: Political sociology; Ethnicity; Social policy; Migration; Constitutional law; Political Sociology; Ethnicity Studies; Social Policy; Migration; Social Structure, Social Inequality; Constitutional Law